Peningkatan Pemanfaatan Tanaman Toga Penangkal Covid-19 Pada Kader Toga Puskesmas Kemuningsari Kidul Jember - Desi Sandra Sari; Iis Rahmawati; Leersia Yusi (Dental Agromedis, 2024)
The problems of the community in the area of the Kemuningsari Kidul Public Health Center, Jenggawah, Jember are that they still do not use the yard with the toga plant optimally, the knowledge of the residents is still low, the lack of community resources and limited information and technology. During this pandemic, it is very important to maintain general health and increase body resistance to prevent the entry of the Covid-19 virus. This study aims to increase health knowledge, skills and use of the toga plant in the community independently through empowering toga cadres to behave in a healthy life during a pandemic in the Kemuningsari Kidul Public Health Center, Jenggawah, Jember. The solutions offered are counselling the benefits of the toga plant for endurance to prevent Covid-19 disease to toga cadres, public awareness through Toga cadres on the importance of maintaining body resistance by consuming the toga plant as a food supplement. Problem-solving from partners is carried out with a community service scheme. with the stages of providing counselling on the benefits of the Toga plant for endurance to prevent Covid 19 disease to Toga cadres, making the community aware through the Toga cadres of the importance of maintaining body resistance by consuming the Toga plant as an alternative to cheap, practical food supplements and training on how to use the Toga plant.Keywords: Toga Cadres, Immunity System, Covid-19, Kemuningsari Kidul Jember.